Pelatihan Public Speaking Bagi Karang Taruna Dharma Bakti Kelurahan Renon - I Gusti Ayu Agung Istri Sari Dewi; Ni Luh Putu Ning Septyarini Putri Astawa; Ni Kadek Sintya (STMIK Royal, 2022)
Abstract: Public speaking is an important skill for every person and organization to have. In doing public speaking, it takes careful practice to get used to convey a topic in front of many people. However, in reality, many people and youth have low public speaking skills, which makes it difficult for them to express their opinions in front of many people, so a public speaking training for youth groups is held so that participants who take part in the training understand the importance of having public speaking skills and how to improve these skills. . In addition, this public speaking training is needed in youth organizations so that in internal and external communication there is no miscommunication and expressing opinions. The method used in this activity is a participatory act review. This activity received a positive response from the participants, as seen from the enthusiasm of the participants and active in asking, discussing, and answering questions posed by the presenters. In addition, based on the Pre-Test and Post-Test questionnaires that have been given to 22 training participants, the results are very good. Where based on the post-test filled by 22 people, there are 17 people who get good results with a vulnerable value of 76-100, only 5 people with a value (56-75) this shows much improvement from the results of the previous pre-test, which only 5 people get good gradesKeywords: public speaking; training; youth organization.Abstrak: Public speaking merupakan skill yang penting untuk dimiliki oleh setiap orang maupun organisasi. Dalam melakukan public speaking dibutuhkan latihan yang matang agar terbiasa dalam menyampaikan suatu topik di depan banyak orang. Namun kenyataannya, banyak masyarakat maupun pemuda yang memiliki kemampuan public speaking rendah, yang menyebabkan mereka sulit menyampaikan pendapat di depan banyak orang, maka diadakanlah pelatihan public speaking bagi karang taruna ini agar peserta yang mengikuti pelatihan memahami pentingnya mempunyai keterampilan public speaking dan bagaimana meningkatkan keterampilan tersebut. Selain itu, pelatihan public speaking ini diperlukan dalam organisasi karang taruna agar dalam komunikasi internal maupun eksternal tidak terjadinya miscommunication dan menyampaikan pendapat. Metode yang digunakan dalam kegiatan ini adalah kaji tindak partisipati. Kegiatan ini mendapatkan respon yang positif dari peserta, yang dilihat dari antusiasme para peserta dan aktif dalam bertanya, berdiskusi, dan menjawab pertanyaan yang dilontarkan oleh pemateri. Selain itu, berdasarkan angket pengisian Pre-Test dan Post Test yang sudah diberikan kepada 22 peserta pelatihan menunjukan hasil yang sangat baik. Dimana berdasarkan post-test yang diisi oleh 22 orang terdapat 17 orang yang mendapatkan hasil baik dengan rentan nilai 76-100, cukup 5 orang dengan nilai (56-75) hal ini jauh menunjukan peningkatan dari hasil pre-test sebelumnya, yang hanya 5 orang mendapat nilai baikKata kunci: karang taruna; pelatihan; public speaking.